Pendampingan dalam Meningkatkan Potensi Kreatifitas dari Anak-Anak Berkebutuhan Khusus - Astarini, Dewa Ayu Oki; Murapi, Ikang; khairunnisa, Khairunnisa; Aryani, R Ayu Ida (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
This service activity aims to provide education regarding Assistance in Increasing the Creative Potential of Children with Special Needs at Pelangi Lombokcare Special School (SLB). This activity is a form of humanity to introduce to the community more specifically to students to increase social feeling, as a form of caring and sharing enthusiasm for extraordinary friends, and to help provide assistance and encouragement to increase creativity for children with special needs. This service is carried out in the form of events such as education on saving and arithmetic, puzzle games and coloring, music entertainment and giving souvenirs so that the benefits that can be obtained from this activity are being able to contribute to the development of extraordinary friends which will have an impact on increasing the ability to be creative. In addition, the activities we carry out aim to help extraordinary friends discover their talents and interests. The activities carried out are also sustainable, so that in the future there will be similar activities to be carried out as well.